Lung Marginated and Splenic Murine Resident Neutrophils Constitute Pioneers in Tissue-Defense During Systemic E. coli Challenge - Juzenaite, Goda; Secklehner, Judith; Vuononvirta, Juho; Helbawi, Yoseph; Mackey, John B. G.; Dean, Charlotte; Harker, James A.; Carlin, Leo M.; Rankin, Sara; De Filippo, Katia (Frontiers in Immunology, 2021)
The rapid response of neutrophils throughout the body to a systemic challenge is a critical first step in resolution of bacterial infection such as Escherichia coli (E. coli). Here we delineated the dynamics of this response, revealing novel insights into the molecular mechanisms using lung and spleen intravital microscopy and 3D ex vivo culture of living precision cut splenic slices in combination with fluorescent labelling of endogenous leukocytes. Within seconds after challenge, intravascular marginated neutrophils and lung endothelial cells (ECs) work cooperatively to capture pathogens. Neutrophils retained on lung ECs slow their velocity and aggregate in clusters that enlarge as circulating neutrophils carrying E. coli stop within the microvasculature. The absolute number of splenic neutrophils does not change following challenge; however, neutrophils increase their velocity, migrate to the marginal zone (MZ) and form clusters. Irrespective of their location all neutrophils capturing heat-inactivated E. coli take on an activated phenotype showing increasing surface CD11b. At a molecular level we show that neutralisation of ICAM-1 results in splenic neutrophil redistribution to the MZ under homeostasis. Following challenge, splenic levels of CXCL12 and ICAM-1 are reduced allowing neutrophils to migrate to the MZ in a CD29-integrin dependent manner, where the enlargement of splenic neutrophil clusters is CXCR2-CXCL2 dependent. We show directly molecular mechanisms that allow tissue resident neutrophils to provide the first lines of antimicrobial defence by capturing circulating E. coli and forming clusters both in the microvessels of the lung and in the parenchyma of the spleen.